CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If 2f (x) − 3f1x=x2 (x ≠ 0), then f(2) is equal to

(a) -74
(b) 52
(c) −1
(d) None of these


Solution

(a) -74
 
2f (x) − 3f1x=x2         (x ≠ 0)                  ....(1)
Replacing x by 1x:2f1x-3f(x) = 1x2            ...(2) Solving equations (1) & (2) -5f(x) = 3x2+2x2f(x)  = -15 3x2+2x2Thus, f(2) = -15 34+2×4= -15 3+324 = -74

Mathematics
RD Sharma XI (2015)
Standard XI

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
Same exercise questions
View More


similar_icon
People also searched for
View More



footer-image